Semantic Displacement In Ibn Zamrak’s Poems Of Longing As A Selection: Analytical and Applied Reading/ الانزياح الدلالي في قصائد الشوق لابن زمرك: قراءة تحليلية وتطبيقية - Abdulrahman Abdulsalam Dawood (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research addresses the topic of semantic displacement through an analytical reading of a poem by the Andalusian poet Ibn Zamrak. It focuses on the artistic techniques employed by the poet to transform meanings from their direct denotations into metaphorical and symbolic ones that express the depth of emotional experience. The study begins by defining the concept of displacement linguistically and terminologically, then emphasizes semantic displacement as one of the most prominent tools of aesthetic expression in poetic texts. Relying on a detailed analysis of the poem’s structure, the study reveals a complex network of poetic images and displacements used by the poet to express longing and nostalgia, which contributed to reshaping meaning and expanding the horizon of reception. The analysis shows that semantic displacement is not merely a means of rhetorical embellishment but an effective tool in constructing the text and shaping its poetic vision. The poem was selected for its semantic and expressive density, as well as for the rich artistic model it offers to study the relationship between displacement and meaning. The research concludes that Ibn Zamrak possesses a remarkable ability to employ language in a way that transports the reader from the real world to a poetic realm filled with emotion and beauty. This study contributes to a deeper understanding of the role of semantic displacement in Arabic poetry and highlights Ibn Zamrak’s distinguished position within the Andalusian literary heritage.